Stabilization of three-dimensional charge order through interplanar orbital hybridization in PrxY1-xBa2Cu3O6+δ - Ruiz, Alejandro; Gunn, Brandon; Lu, Yi; Sasmal, Kalyan; Moir, Camilla M.; Basak, Rourav; Huang, Hai; Lee, Jun-Sik; Rodolakis, Fanny; Boyle, Timothy J.; Walker, Morgan; He, Yu; et al. (Arxiv, 2022)
The shape of 3d-orbitals often governs the electronic and magnetic properties of correlated transition metal oxides. In the superconducting cuprates, the planar confinement of the dx2−y2 orbital dictates the two-dimensional nature of the unconventional superconductivity and a competing charge order. Achieving orbital-specific control of the electronic structure to allow coupling pathways across adjacent planes would enable direct assessment of the role of dimensionality in the intertwined orders. Using Cu-L3 and Pr-M5 resonant x-ray scattering and first principles calculations, we report a highly correlated three-dimensional charge order in Pr-substituted YBa2Cu3O7, where the Pr f -electrons create a direct orbital bridge between CuO2 planes. With this we demonstrate that interplanar orbital engineering can be used to surgically control electronic phases in correlated oxides and other layered materials.
Im Titel erscheinen die folgenden Zeichen und Begriffe tiefgestellt: x, 1-x, 2, 3, 6+δ
Gesehen am 11.01.2024